Multicenter Retrospective Analysis of Chemotherapy for Advanced Pancreatic Acinar Cell Carcinoma: Potential Efficacy of Platinum- and Irinotecan-Containing Regimens. Issue 1 (January 2021) - Takahashi, Hideaki; Ikeda, Masafumi; Shiba, Satoshi; Imaoka, Hiroshi; Todaka, Akiko; Shioji, Kazuhiko; Yane, Kei; Kojima, Yasushi; Kobayashi, Satoshi; Asagi, Akinori; Ozaka, Masato; Takada, Ryoji; et al.
Abstract : Objectives: The aim of this multicenter retrospective study was to identify the optimal chemotherapeutic regimen for advanced pancreatic acinar cell carcinoma (PACC). Methods: Fifty-eight patients with histopathologically confirmed advanced PACC who had received chemotherapy between 1996 and 2013 were enrolled. The clinical characteristics of the patients and the treatment efficacy data were collected from the medical records at 16 Japanese institutions, using standardized data collection instrument. Results: The most commonly selected treatment regimens were gemcitabine-, fluoropyrimidine-, platinum-, and irinotecan-containing regimens. The overall response rate in the patients who received first-line chemotherapy were 7% and 38%, respectively, and the median overall survival was 13.2 months. When the data for all the treatment lines were aggregated, the response rates to gemcitabine-, fluoropyrimidine-, platinum-, and irinotecan-containing regimens were 7%, 18%, 40%, and 29%, respectively. The overall survival tended to be better in patients who had received a platinum-containing regimen (hazard ratio, 0.50; 95% confidence interval, 0.23–1.11; P = 0.08) or irinotecan-containing regimen (hazard ratio, 0.42; 95% confidence interval, 0.15–1.19; P = 0.09) at least once in the treatment course as compared with those who had not. Conclusions: Our findings suggested that platinum- and irinotecan-containing regimens exhibited some potential efficacy in patients with advanced PACC.